FORMATION OF SALT STRUCTURES ON THE CONTINENTAL MARGINS - Konishchev V.S.; Volozh Yu.A. (My University, 1990)
In the study of the continental margins by marine seismic exploration methods, it has been established that the shelf and continental slope of many passive margins contain widespread evaporite associations and salt-diapir structures. The distinctive structure and development of the continental margins have left their stamp on the formation and structure of the salt-diapir structures occurring in them. Predominantly slightly manifested salt diapiroids (salt pillows) are developed on the inner shelf, near the line where the salt-bearing formations pinch out. On the continental slopes, these deposits have a considerable primary sedimentary dip toward the ocean, which results in the development of large slumps and slides that also involve the salt-bearing deposits and give rise to halokinesis within them. The considerable sedimentational reduction in thicknesses of the suprasalt deposits down the continental slope has given rise to large gradients of their overburden pressure on the evaporite series and caused the salt to flow toward the ocean, impelled by the gravitational factor of halokinesis.